The effect of acceptance and commitment therapy on depression in parents of children with special needs: a meta-analysis - Wang, Wei; He, Haoran (Frontiers in Psychology, 2025)
PurposeThis study aimed to evaluate the effectiveness of Acceptance and Commitment Therapy (ACT) in alleviating depressive symptoms among parents of children with special needs. Additionally, it examined the moderating effects of geographic and cultural contexts, intervention parameters, and types of children’s diseases.MethodsA systematic search was conducted in PubMed, Web of Science, and the Cochrane Library. Inclusion criteria were: (1) peer-reviewed studies published in English, (2) randomized controlled trials (RCTs), (3) ACT as the core intervention, (4) participation by parents of children with special needs, and (5) reporting of standardized effect sizes for depressive symptoms. A total of 12 studies (n = 746) met the eligibility criteria. A fixed-effects model was employed for the meta-analysis, and subgroup analyses were conducted based on geographic distribution, intervention duration, intervention parameters, and types of children’s diseases (neurodevelopmental disorders, chronic illnesses, or severe conditions).ResultsACT significantly reduced depressive symptoms (SMD = −0.36, 95% CI [−0.51, −0.22], p < 0.0001). Subgroup analyses indicated that the parents of children with neurodevelopmental disorders or chronic illnesses, the national context, and the frequency of intervention were key sources of heterogeneity in treatment outcomes.ConclusionThe synthesized evidence suggests that ACT is particularly beneficial for parents of children with neurodevelopmental disorders and chronic illnesses. A recommended intervention duration of 4–8 weeks (≥35 min per session, 1–2 sessions per week) is optimal, and the effect may be the most significant in areas with a well-developed welfare system. Future studies should prioritize the development of culturally adapted intervention modules and explore digital health platforms to enhance accessibility.